Fundamentals of crime mapping - Paynich, Rebecca (Jones and Bartlett Publishers, 2009)
An introduction to crime mapping -- Social disorganization and social efficacy -- Environmental criminology -- Geography and individual decision-making : victims and offenders -- Research and applications in crime mapping -- Crime mapping and analysis data -- People and places : current crime trends -- A brief review of statistics -- Distance analysis -- Hot spot analysis